Regulatory SNP of RREB1 is Associated With Bone Mineral Density in Chinese Postmenopausal Osteoporosis Patients - Feng, Shuo; Wang, Han; Yan, Yumeng; Su, Xin; Ao, Jintao; Chen, Wei (Frontiers in Genetics, 2021)
Postmenopausal osteoporosis (PMO) is the most common bone disorder in elderly Chinese women. Although genetic factors have been shown to have a pivotal role in PMO, studies on genetic loci associated with PMO in Chinese individuals are still lacking. We aimed to identify SNPs that contribute to PMO in Chinese individuals by conducting a genome-wide association study (GWAS). Bone mineral density (BMD) of postmenopausal Chinese women was assessed. Participants with T-score <2.5 standard deviations (n=341) were recruited and divided into a discovery group (n=150) and a replication group (n=191). GWAS was performed, with T-score as the quantitative trait, using linear regression. Our results revealed that an SNP cluster upstream of RREB1 showed a trend of association with BMD in Chinese PMO patients. The leading SNP of the cluster was rs475011 (pcombined=1.15×10-6, beta=0.51), which is a splicing quantitative trait locus (sQTL) of RREB1. This association was further supported by data from the UK Biobank (UKBB; p = 9.56×10-12). The high BMD-associated allele G of rs475011 is related to a high intron excision ratio. This SNP may increase BMD by upregulating mature RREB1 mRNA, based on data from the Genotype-Tissue Expression (GTEx) database. We identified BMD-associated SNPs that regulate RREB1 in Chinese PMO patients. Future functional experiments are needed to further link rs475011, RREB1, and PMO in Chinese individuals.